Reported Social Unrest Index : March 2022 Update - Barrett, Philip (IMF Working Papers; Working Paper ;, 2022)
This paper updates the Reported Social Unrest Index of Barrett et al (2020), reviewing recent developments in social unrest worldwide since the start of the COVID-19 Pandemic. It shows that unrest was elevated during late 2019, coincident with widespread protests in Latin America. Unrest then fell markedly during the early stages of the pandemic as voluntary and involuntary social distancing struck. Social unrest has since returned but generally remains below levels seen in 2019.